BONY SHUTTLE PIN SPLINT - Shnain, H.; R. Khalid, F.; H. Markus, N. (The Iraqi Journal of Veterinary Medicine, 1989)
Fifteen bony shuttle pins are used to immobilize induced radial and tibial fractures in the distal third. Good alignment and healing are by radiological examination. There is no side effect due to application of such kind of splints which are eventually resorbed.